3D Printing of UV-Curable Polyurethane Incorporated with Surface-Grafted Nanocellulose - Mohan, Denesh (Nanomaterials (Basel), 2019)
The recognition of nanocellulose has been prominent in recent years as prospect materials, yet the ineffectiveness of nanocellulose to disperse in an organic solvent has restricted its utilization, especially as a reinforcement in polymer nanocomposite. In this study, cellulose has been isolated and defibrillated as cellulose nanofibrils (CNF) from oil palm empty fruit bunch (EFB) fibers. Subsequently, to enhance its compatibility with UV-curable polyurethane (PU)-based resin, the surface hydrophilicity of CNF has been tailored with polyethylene glycol (PEG), as well as reduced graphene oxide (rGO). The dispersibility of reinforced modified CNF in UV-curable PU was examined through the transmittance interruption of resin, chemical, and mechanical properties of the composite printed using the stereolithographic technique. Evidently, the enhanced compatibility of modified CNF and UV-curable PU was shown to improve the tensile strength and hardness of the composites by 37% and 129%, respectively.